How’d They Do? Exploring experts’ past opinions of College Radio’s future - Freeman, Bradley C. (Routledge, 2020)
Predicting the future of college radio is no easy task. There are a lot of factors to consider. If you are going to attempt to make predictions, it helps to have people who are knowledgeable and experienced with the subject. In 2003, a study in the Journal of Radio Studies (precursor to JRAM), employed a Delphi Method to gather the thoughts and opinions of college radio advisors on the future of the medium. With the benefit of hindsight, we can now have a look at the success rate of their prognostications. The 2003 study presented several areas of investigation, before ultimately indicating five main trends. The present study utilizes secondary analysis and observation in an attempt to evaluate the predictions. The limitations of the Delphi Method in the first study are noted, as is the lack of data availability in providing a thorough review for the present study. Nevertheless, presented here is a review of the predicted trends from 2003. How did they do?